Morcellation of occult uterine malignancies: an Australian single institution retrospective study. (28th August 2015) - Tan, Adeline; Salfinger, Stuart; Tan, Jason; Cohen, Paul
<x xml:space="preserve">Abstract</x> Introduction Morcellation for tissue extraction during laparoscopic hysterectomy or myomectomy has recently been questioned because of the potential to spread occult uterine cancers. The Australian Therapeutic Goods Administration (TGA) issued a safety advisory in August 2014, estimating the risk of occult malignancy in the Australian population to be one in 1000 or lower, based on estimates from overseas studies in the absence of any local data. Aims The aim of this study was to determine the incidence of occult uterine malignancies in morcellated surgical specimens at St John of God Hospital in Perth, Western Australia. Materials and Methods All women who had a hysterectomy or myomectomy with morcellation of the surgical specimen for presumed benign uterine fibroids at our institution from 01 November 2009 to 12 March 2015 were identified and stratified into benign disease, uncertain malignant potential and malignant. Results Seven hundred and thirty‐four women were included, and three malignancies were identified: two cases with leiomyosarcoma (LMS) and another with an endometrioid endometrial adenocarcinoma (EAC). One case of serous tubal in situ carcinoma (STIC) and two cases of benign metastasising leiomyoma/leiomyomatosis were also identified. The overall risk of malignancy in a morcellated surgical specimen was 0.41% (three in 734). The risk of morcellating an incidental uterine malignancy was 0.27% for LMS and 0.14% for EAC. All three incidental malignancies were diagnosed in premenopausal women. Conclusions The risk of unintended morcellation of uterine malignancy in our study is higher than that estimated by the Australian TGA and highlights the urgent need for further studies in Australia.